The Effect of Workload and Work Stress on Employee Performance Mediated by Job Satisfaction: An Empirical Study of Employees of the Indonesian Aviation Academy (API) Banyuwangi - Iswahyudi, Prasetyo; Nur Halimah; Miko Andi Wardana; Khoirunnisa Larasati; Hendra Sudarso (PT Inovasi Pratama Internasional, 2025)
This research is motivated by the problem of stagnant employee performance at the Indonesian Aviation Academy (API) Banyuwangi, influenced by an unbalanced workload and high levels of job stress. This condition has resulted in decreased productivity and performance accountability, which are mostly in the adequate category. Job satisfaction is suspected to be an important mediating variable in the relationship between workload, job stress, and employee performance, so empirical research is needed to find appropriate managerial solutions. The research method uses a quantitative approach with an explanatory research design. The independent variables in this study include workload (X1) and work stress (X2), while the mediating variable is job satisfaction (Y1) and the dependent variable is employee performance (Y2). Data were obtained through distributing questionnaires to employees of the Indonesian Aviation Academy (API) Banyuwangi using a purposive sampling technique, then analyzed to test the relationship between variables and the mediating role of job satisfaction. The research findings are expected to contribute both theoretically and practically. Theoretically, this study enriches human resource management studies related to the influence of workload and job stress on performance by considering the mediating role of job satisfaction. Practically, the findings of this study can serve as a reference for the management of the Indonesian Aviation Academy (API) Banyuwangi in formulating strategic policies, particularly in creating a balanced work environment, reducing stress levels, and increasing employee job satisfaction to encourage more optimal performance.